2007
DOI: 10.1108/01425450710720020
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence at work: links to conflict and innovation

Abstract: Purpose -This paper aims at exploring, for the first time in the Arab World, the role of emotional intelligence (EI) in affecting work outcomes. Design/methodology/approach -A self-administered questionnaire was used to survey 500 employees from 19 organizations in the United Arab Emirates. The findings are discussed in the paper along with some recommendations for managers and researchers. Findings -The results revealed significant differences between employees' perceptions of emotional intelligence, conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 23 publications
(15 reference statements)
3
64
0
3
Order By: Relevance
“…Following the emotional intelligence theory, individuals' intelligence quotient (IQ) alone cannot explain the variation in their job performance, and thus the effects of other factors such as emotional intelligence should be also considered (Jamali et al, 2008;Suliman and Al-Shaikh, 2007). Although no consensus exists on the definition of emotional intelligence, scholars agree that it is a strong predictor of performance both at the individual and organizational levels (Koman and Wolff, 2008).…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
“…Following the emotional intelligence theory, individuals' intelligence quotient (IQ) alone cannot explain the variation in their job performance, and thus the effects of other factors such as emotional intelligence should be also considered (Jamali et al, 2008;Suliman and Al-Shaikh, 2007). Although no consensus exists on the definition of emotional intelligence, scholars agree that it is a strong predictor of performance both at the individual and organizational levels (Koman and Wolff, 2008).…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%
“…The finding is according to (Dulewicz et al, 2003) that found managers' emotional intelligence correlated positively with quality of work life and morale, also (Brackett et al, 2004) concluded that low scores on EI were associated with poor quality peer relations. (Suliman & Al-Shaikh, 2007) revealed that employees with higher levels of EI were found to report higher levels of readiness to create and innovate. Results also favor the same and this finding was also supported by (Tischler et al, 2002) he examined the linking emotional intelligence, spirituality and work place performance and displayed a positive relationship between emotional intelligence and work place success and also by (Cooper & Sawaf, 1997;Megerian & Sosik, 1996;Wright and Staw, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that EI is related to innovation and creativity (Stough & De Guara, 2003;Suliman & Al-Shaikh, 2006). Employees with high EI will engage in high innovator role but employees with low EI will perform low innovator role.…”
Section: The Moderating Effects Of Service Types On the Relationshipsmentioning
confidence: 99%
“…Those having high EI abilities tend to be innovative and creative (Suliman & Al-Shaikh, 2006). Emotionally intelligent employees are able to identify their true feelings, understand the causes and consequences of the feelings, and manage as well as use the feelings to find creative solutions for the existing problems.…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation